Population‐based incidence and clinical characteristics of idiopathic intracranial hypertension. (28th February 2017) - Sundholm, A.; Burkill, S.; Sveinsson, O.; Piehl, F.; Bahmanyar, S.; Nilsson Remahl, A. I. M.
Abstract : Objective: To validate the diagnosis of idiopathic intracranial hypertension (IIH) from the Swedish National Patient Register (NPR) and investigate the incidence of IIH, as well as co‐morbidities and medication use in a large Swedish population‐based sample. Methods: We searched the NPR to find all patients ≥18 years old with the ICD‐10 diagnosis code (G93.2) for IIH in Stockholm County from Jan 1, 2006, to Dec 31, 2013. All medical records were reviewed to validate the diagnosis and to collect additional information. Results: We included 207 patients with an IIH diagnosis, of which 135 (65%) were correctly diagnosed when validated by charts review. Eighty‐three patients had disease onset during the study period. This gave a yearly incidence of 0.65/100 000. Female‐to‐male ratio was 6.1:1. Females, mean age 31.0 (CI 28.8‐33.1), were younger at time of diagnosis compared to males, mean age 42.9 (CI 36.4‐49.5), P <.001. The most common co‐morbidities were obesity (92%), hormonal conditions (21%) and recent infections preceding the diagnosis (21%). Prior treatment with tetracycline derivatives were seen in 9%. Conclusion: The incidence of IIH in Stockholm is in the lower range of previously reported rates, possibly due to a lower prevalence of obesity. A substantial proportion of patients (35%) did not fulfill diagnostic criteria. Disease onset occurs at younger age in females. Co‐morbidities were mainly associated with diseases affecting hormonal balance or causing inflammatory activation. These findings raise new hypothetical theories regarding mechanisms involved in IIH pathogenesis.